2021
DOI: 10.1002/advs.202102534
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear AIM2‐Like Receptors Drive Genotoxic Tissue Injury by Inhibiting DNA Repair

Abstract: Radiation is an essential preparative procedure for bone marrow (BM) transplantation and cancer treatment. The therapeutic efficacy of radiation and associated toxicity varies from patient to patient, making it difficult to prescribe an optimal patient-specific irradiation dose. The molecular determinants of radiation response remain unclear. AIM2-like receptors (ALRs) are key players in innate immunity and determine the course of infections, inflammatory diseases, senescence, and cancer. Here it is reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Two successive oligonucleotide/oligosaccharide folds of the HIN-200 domain bind long double-strand DNA (dsDNA) fragments deriving from damaged nuclear and/or mitochondrial DNA or from infecting bacterial or viral pathogens (Veeranki and Choubey 2012). The HIN-200 domain also binds intranuclear DNA damaged sites (Hu B and others 2016; Jiang and others 2021).…”
Section: Absent In Melanoma 2 (Aim2/aim2) Inflammasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two successive oligonucleotide/oligosaccharide folds of the HIN-200 domain bind long double-strand DNA (dsDNA) fragments deriving from damaged nuclear and/or mitochondrial DNA or from infecting bacterial or viral pathogens (Veeranki and Choubey 2012). The HIN-200 domain also binds intranuclear DNA damaged sites (Hu B and others 2016; Jiang and others 2021).…”
Section: Absent In Melanoma 2 (Aim2/aim2) Inflammasomesmentioning
confidence: 99%
“…ALR -knockout mice resisted such irradiation injuries, revealing that the AIM2 inflammasome assembles inside DNA-damaged nuclei and binds DNA harm sites, thereby inhibiting the DNA unpacking, which is crucially needed for DNA repair to occur. Consequently, ALR s advance genome instability, micronucleus formation, and cell death in ways disconnected from their innate immunity roles (Jiang and others 2021). Whether this mechanism operates within irradiated human brain cell nuclei remains to be ascertained.…”
Section: Absent In Melanoma 2 (Aim2/aim2) Inflammasomesmentioning
confidence: 99%
“…Recent studies reveal that ALRs perform different functions outside the immune system. It has been demonstrated that DNA breaks are repaired more efficiently in mice and cells lacking ALRs (ALR −/− mice lack the entire ALR locus containing all 13 ALR genes on Chromosome 13), resulting in the stronger resistance to the genotoxic effects of irradiation and chemotherapy ( Brunette et al, 2012 ; Gray et al, 2016 ; Jiang et al, 2021 ). Mechanistically, nuclear ALRs limit DNA repair machinery access to damaged sites by binding the chromatin, and self-oligomerization promoted chromatin compaction.…”
Section: The Impacts Of Nucleic Acid-sensing Pathways On Dna Repairmentioning
confidence: 99%
“…Toby Lawrence, King's College London and CIML, Marseilles, presented work exploring tumour heterogeneity directing his studies to myeloid cells and their diverse and divergent roles in defining tumour survival or suppression 3 . Moreover, Nelson Gekara, Wenner‐Gren Institute, Stockholm University, elucidated the role of the innate immune system in sensing DNA repair activity, as a central regulatory mechanism of health maintenance 4,5 . Immunologists, neurologists and psychologists are becoming increasingly aware of the importance of crosstalk between the immune system and the nervous system.…”
Section: In‐depth Immunology – From Basic Concepts To Vaccine Develop...mentioning
confidence: 99%
“…3 Moreover, Nelson Gekara, Wenner-Gren Institute, Stockholm University, elucidated the role of the innate immune system in sensing DNA repair activity, as a central regulatory mechanism of health maintenance. 4,5 Immunologists, neurologists and psychologists are becoming increasingly aware of the importance of crosstalk between the immune system and the nervous system. David Engblom, Center for Social and Affective Neuroscience, Linköping University, presented his fascinating work, including unpublished findings, exploring immune signalling triggered by psychological distress.…”
Section: In-depth Immunology -From Basic Concepts To Vaccine Developm...mentioning
confidence: 99%